Application of AHP-SAW Based Decision Support System for Objective and Comprehensive Junior High School Student Selection - Sheptian, Riky; Dwi Rismi Ocy; Eny Cahyaningsih; Iva Syarifah; Achmad Ridwan (PT. Banjarese Pacific Indonesia, 2025)
The admission process in Integrated Islamic Junior High Schools (SMPIT) often faces challenges of subjectivity, inefficiency, and lack of transparency in determining selection results. This can lead to inappropriate student placement and decreased trust from stakeholders. This study aims to develop a Decision Support System (DSS) based on a combination of Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW) to improve objectivity and accountability in student selection. AHP is used to determine the weights of the four main academic criteria-the report card scores of Mathematics, Science, Indonesian, and English-based on consistent expert judgment. Furthermore, the SAW method processes the normalized and weighted scores to produce a final ranking of 100 prospective students. The implementation results show that the AHP-SAW integration is able to produce quantitative, transparent, and data-based rankings, thus minimizing subjectivity in the selection process. It provides a structured and replicable model, supporting fairness and efficiency in student admission. This approach is relevant to be applied in educational institutions that want to align the selection process with Islamic educational values and multi-criteria-based objectivity principles.